Studi Deskriptif: Status Gizi, Kadar Hb Pada Ibu Nifas Hari Ke-1 Sampai Hari Ke-7 Dengan Luka Perineum - Oktari, Ida Ayu; Wijayanti, Krisdiana; Anwar, M. Choiroel (Universitas Malahayati, 2025)
ABSTRACT Perineal suture wounds occur in 75% of mothers who give birth normally. Wound healing is a quality of tissue life, itis also related to tissue regeneration. Age, position, tissue management, proper nutrition, hb levels, hygiene, andrest. Poor nutritional status or maternal nutrition will potentially slow down wound healing. To determine the description of nutritional status and hb levels of postpartum mothers on the 1st day to the 7th day with perineallesions. Descriptive analytical research and using a cross-sectional study design. The results of the study of Hb levelsof postpartum mothers with perineal wounds that were not anemia were 79.4%, mild anemia was 14.7%. Thenutritional status of protein intake deficit was 17.6%, normal protein intake was 35.2%, fe intake was 35.2%, and feintake was 44.1%. The nutritional status and hb levels of postpartum mothers with perineal wounds are necessaryduring the healing period of perineal wounds, and a good nutritional balance is achieved through adequatenutritional intake, in the form of eating and drinking within a 24-hour period containing calories, protein and fe. Keywords : Nutritional Status, Hb, Perineal Wounds, Postpartum ABSTRAK Luka jahitan perineum terjadi pada 75% ibu yang melahirkan secara normal. Penyembuhan luka adalah suatu kualitas dari kehidupan jaringan, hal ini juga terkait dengan regenerasi jaringan. Usia, posisi, penatalaksanaan jaringan, nutrisi yang tepat, kadar hb, kebersihan, dan istirahat. Status gizi atau nutrisi ibu yang kurang baik akan berpotensi memperlambat penyembuhan luka. Mengetahui gambaran status gizi dan kadar hb ibu nifas hari ke-1 samapai hari ke-7 dengan luka perineum. Penelitian analitik deskriptif dan menggunakan desain studi cross secsional. Hasil penelitian kadar Hb ibu nifas dengan luka perineum yang tidak anemia 79,4%, anemia ringan 14,7%. Status gizi intake protein deficit berat 17,6%, intake protein normal 35,2%, intake fe cukup 35,2%, dan intake fe kurang 44,1%. Status gizi dan kadar hb ibu nifas dengan luka perineum diperlukan pada masa penyembuhan luka perineum, dan keseimbangan gizi yang baik tercapai melalui asupan gizi yang memadai, berupa makan dan minuman dalam periode 24 jam mengandung kalori, protein dan fe. Kata Kunci: Status Gizi,Hb, Luka Perineum, Nifas